Hospital costs and cost implications of co-morbid conditions for patients with single ventricle in the period through to Fontan completion. (1st August 2017) - Huang, Li; Dalziel, Kim M.; Schilling, Chris; Celermajer, David S.; McNeil, John J.; Winlaw, David; Gentles, Tom; Radford, Dorothy J.; Cheung, Michael; Bullock, Andrew; Wheaton, Gavin R.; Justo, Robert N.; et al.
Abstract: Background: Patients undergoing palliative surgeries for single-ventricle conditions are affected by multiple comorbidities or non-cardiac conditions. The prevalence, costs and the cost implications of these conditions have not been assessed. Methods: Administrative costing records from four hospitals in Australia and New Zealand were linked with the Fontan registry database to analyze the inpatient resource use for co-morbid or non-cardiac conditions. Inpatient costing records from the birth year through to Fontan completion were available for 156 patients. The most frequent primary diagnoses were hypoplastic left heart syndrome (33%), double inlet left ventricle (13%), and tricuspid atresia (12%). Results: During the staged surgical treatment period, children had a mean of 10 ± 6 inpatient admissions and spent 85 ± 64 days in hospital. Among these admissions, 3 ± 5 were for non-cardiac conditions, totaling 21 ± 41 inpatient days. Whilst cardiac surgeries were the major reason for resource use (77% of the total cost), other cardiac care that is not surgical contributed 5% and non-cardiac admissions 18% of the total cost. The three most prevalent non-cardiac diagnostic admission categories were 'Respiratory system', 'Digestive system', and 'Ear, nose, mouth and throat', affecting 28%, 21% and 34% of the patients respectively. Multivariate regression estimated that admissions for each of these categories resulted in an increased cost of 34, 563 ( P = 0.08), 52, 438 ( P = 0.05) and 10, 525 ( P = 0.53) per patient respectively for the staged surgical treatment period. Conclusions: Non-cardiac admissions for single-ventricle patients are common and have substantial resource implications. Further research assessing the causes of admission and extent to which admissions are preventable is warranted.